Socio-demographic and lifestyle determinants of the micronutrients status during pregnancy. (13th November 2019) - Polanska, K; Trafalska, E; Hanke, W; Wesolowska, E; Jankowska, A; Kaluzny, P; Janasik, B; Gromadzinska, J; Wasowicz, W; Calamandrei, G
Abstract: : Micronutrients status during pregnancy is recognized as one of the environmental factors that can have an impact on maternal and children's health. The study aims at evaluating sociodemographic, lifestyle, environmental, and pregnancy-related determinants of maternal micronutrients status during pregnancy. The analysis was based on data from the Polish Mother and Child Cohort (REPRO_PL). During the second trimester of pregnancy, 1306 women filled in a modified version of the validated food frequency questionnaire (FFQ) based on which the intake of the following micronutrients was estimated: calcium, magnesium, zinc, copper, selenium, folate, vitamin D, vitamin A and vitamin E. In addition, copper, zinc and selenium levels were measured in the blood collected during the second trimester of pregnancy. About 95% of the women took dietary supplements during pregnancy. Despite such supplementation in the case of a high proportion of the women the intake of majority of the analyzed micronutrients was below recommendations for the pregnancy period (based on the Estimated Average Requirement). The mean plasma zinc, copper and selenium concentrations were 0.9±0.3 mg/l, 2.0±0.6 mg/l and 48.4±10.5 ug/l, respectively. The chance to reach the recommended intake for vitamin A, vitamin D and selenium was higher among the multiparous women (OR = 1.53 p = 0.007; OR = 1.44 p = 0.02; OR = 1.48 p = 0.009) and for zinc among the women with a higher socio-economic status (SES) (OR = 1.43 p = 0.04). For other variables the results were not statistically significant. A higher selenium level in the plasma was observed among the older women (p = 0.01) and those with a higher SES (p = 0.03). The current study presents evidence on specific factors influencing the micronutrients intake. They need to be accounted for in educational programs and interventions that focus on healthy diet recommendations during pregnancy. Key messages: In the case of a high proportion of the women the intake of majority of the analyzed micronutrients was below recommendations for the pregnancy period. More effort should be taken to educational programs and interventions that focus on healthy diet recommendations during pregnancy.